Preparation method of starch slurry applied to Jinshuibao tablets and preparation method of preparation of Jinshuibao tablets
By using corn starch instead of gelatin liquid as a binder during the preparation process of Jinshuibao tablets and optimizing the preparation method of starch slurry, the problem of solid but easy edge loss in the prior art is solved, and the reputation of the product and the trust of the patient are improved.
Patent Information
- Application Number
- CN202411719894.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-11
AI Technical Summary
The existing Jinshuibao tablets use gelatin liquid as a binder during the preparation process, which results in the solid particles produced but easily fall off, affecting the reputation of the product, and the patients have certain psychological resistance to gelatin-containing drugs.
Corn starch is used as a binder to replace gelatin, and the granulation and reputation of Jinshuibao tablets are improved by optimizing the starch slurry preparation method, including adjusting the concentration of starch slurry, preparation method, slurry preparation method and slurry temperature.
By using corn starch as a binder, the prepared Jinshuibao tablets have suitable hardness, qualified weight differences, reasonable disintegration time limit, improved reputation, and eliminated patients' concerns about gelatin, increasing the product's peace of mind.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a type of adhesive suitable for preparing Jinshuibao tablets and a preparation method, and provides a preparation method capable of improving the reputation of Jinshuibao tablets, belonging to the field of medical technology. Background Art
[0002] Jinshuibao Tablets are a type of medicine that contains 0.25 grams of fermented Cordyceps sinensis powder in each tablet. It has the effects of nourishing the kidneys and protecting the lungs, and replenishing essence and qi.
[0003] The existing Jinshuibao tablets use gelatin liquid as an adhesive during the preparation process. Gelatin liquid is currently a commonly used tablet adhesive with strong viscosity and heat-sensitive properties. Its heat-sensitive properties cause the produced particles to be solid and the tablets to easily fall off, thus affecting the reputation of the product. In addition, patients have a certain psychological resistance to drugs containing gelatin.
[0004] To this end, the inventors took the granulation of Jinshuibao tablets, the hardness of plain tablets, weight difference, disintegration time, friability, and reputation as the inspection indicators, and concentrated on trial-producing and screening different types of adhesives in order to obtain adhesives that can replace gelatin. After a large number of screenings, the inventors unexpectedly found that corn starch can replace gelatin and can produce qualified Jinshuibao tablets; and by optimizing the starch slurry preparation method, the reputation of Jinshuibao tablets can be improved. The inventors systematically studied the types, concentrations, preparation methods, slurry preparation methods, and slurry addition temperatures of starch to obtain a new preparation method suitable for Jinshuibao tablets; studied the preparation process of using corn starch slurry to replace gelatin solution, took the granulation of Jinshuibao tablets, angle of repose, bulk density, hardness, weight difference, disintegration time, friability, and reputation as the inspection indicators, screened the amount of oil absorbent used, and the types and amounts of glidants used to obtain the best preparation process. This Jinshuibao tablet preparation process can not only improve the product's reputation, but also eliminate patients' concerns about gelatin, allowing patients to take the product with greater peace of mind. Summary of the invention
[0005] The present invention aims to provide a method for preparing Jinshuibao tablets, which comprises the steps of preparing corn starch slurry; mixing three materials, fermented cordyceps powder, microcrystalline cellulose and silicon dioxide; adding the corn starch slurry into the mixed materials by a slurrying method to prepare a soft material; preparing wet granules; preparing dry granules; granulating; adding magnesium stearate to mix and then tableting.
[0006] In addition to corn starch as a binder, one or more of povidone K30, sodium carboxymethyl cellulose, and hydroxypropyl methylcellulose can also be used as a binder.
[0007] The corn starch slurry is prepared by adding corn starch to water to prepare a corn starch slurry with a weight ratio of 6% to 8%.
[0008] The corn starch slurry is prepared into a corn starch slurry with a temperature of 60-70°C.
[0009] Preferably, in the preparation method of the present invention, the Jinshuibao tablets have the following formula:
[0010] Fermented Cordyceps Powder 1800g
[0011] Silicon dioxide 270g
[0012] Microcrystalline cellulose 780g
[0013] Corn starch slurry 2000g
[0014] Magnesium stearate 30g
[0015] The preparation method comprises the following steps:
[0016] Weigh corn starch, add 2 times the amount of water to dissolve it, and prepare corn starch aqueous solution; slowly pour an appropriate amount of boiling water into the starch aqueous solution, stir while adding until it becomes a paste, and quantitatively adjust to an appropriate amount to prepare 6-8% corn starch slurry; pour fermented cordyceps powder, microcrystalline cellulose, and silicon dioxide into a high-speed mixing granulator and stir and mix to prepare dry mixed powder; slowly add 6-8% corn starch slurry at a temperature of 60-70°C into the dry mixed powder, wet mix, and add an appropriate amount of purified water according to the condition of the soft material to prepare a suitable soft material;
[0017] The soft material is placed in a swing granulator to pass through an 18-mesh screen to obtain wet granules; the wet granules are placed in a stainless steel tray and placed in a constant temperature blast oven to dry the moisture to 4-6%, and then taken out to obtain dry granules; the dry granules are placed in a swing granulator to pass through an 18-mesh screen to granulate;
[0018] Add 0.5 parts of magnesium stearate into the mixture to obtain granules; compress into tablets and apply film coating to obtain the product.
[0019] The technical solution of the present invention is obtained through screening, especially the screening of adhesives, adopting a multi-layer screening principle, including gradient inspection of various indicators. The prepared Jinshuibao tablet particles are screened according to the angle of repose and bulk density of the particles, and the type and amount of the flow aid are screened, thereby obtaining a preparation method for improving Jinshuibao tablets.
[0020] The screening process is as follows:
[0021] Take the raw and auxiliary materials that meet the standards under the prescription of this product, fix the dosage of fermented Cordyceps powder, silicon dioxide, microcrystalline cellulose, and magnesium stearate, use 8% povidone K30 aqueous solution, 3% xanthan gum aqueous solution, 10% monosaccharide syrup, 8% starch slurry, 5% sodium carboxymethyl cellulose aqueous solution, 5% hydroxypropyl methylcellulose aqueous solution, 6% polyoxyethylene aqueous solution, and 10% gelatin solution as adhesives, and prepare granules according to the wet granulation method, press tablets, and coat. The granulation condition, hardness of the plain tablets, weight difference, disintegration time, friability, and reputation (gelatin solution coated tablets are used as the reference, and the evaluation standards are good, medium, and poor) are used as evaluation indicators to screen out the best adhesive. The adhesive screening plan is shown in Table 1, and the quality evaluation is shown in Table 2:
[0022] Table 1 Adhesive screening scheme (unit: g)
[0023]
[0024] Table 2 Quality evaluation
[0025]
[0026]
[0027] The test results show that the soft materials prepared by batches 230301, 230305, 230306 and 230308 are suitable, but the hardness of the plain tablets is average, the weight difference is acceptable, and the reputation evaluation is medium; the soft material prepared by batch 230302 is sticky and has many coarse particles, but the disintegration time is too long and it is unqualified; the soft materials prepared by batches 230303 and 230307 are loose, the wet particles contain more fine powder, the hardness is low, and the reputation evaluation is poor; batch 230304 prepared suitable soft materials, the wet particles are uniform in coarseness and fineness, all tests meet the requirements, and the test indicators are better than those of gelatin liquid samples; therefore, batch 230304 was selected as the best solution, that is, starch slurry is the best adhesive for Jinshuibao tablets.
[0028] Starch type screening
[0029] Take the raw and auxiliary materials that meet the standards under the prescription of this product, fix the amount of fermented Cordyceps powder, silicon dioxide, microcrystalline cellulose, and magnesium stearate, use 8% potato starch, 8% corn starch, and 8% wheat starch as adhesives, and make granules according to the wet granulation method, press tablets, and coat. The granulation condition, tablet hardness, weight difference, disintegration time, brittleness, and reputation are used as evaluation indicators to screen out the best starch type. The starch type screening plan is shown in Table 3, and the quality evaluation is shown in Table 4:
[0030] Table 3 Starch type screening scheme (unit: g)
[0031]
[0032] Table 4 Quality evaluation
[0033]
[0034]
[0035] The test results show that the soft material produced by batch 230309 is sticky, the wet particles contain more coarse particles, and the reputation is evaluated as medium; the soft material produced by batch 230311 is loose, the wet particles contain more fine powder, and the reputation is evaluated as poor; the soft material produced by batch 230311 is suitable, the wet particles are uniform in coarseness and fineness, and the reputation is evaluated as good; therefore, batch 230310 is selected as the best solution, that is, corn starch is the best type of starch.
[0036] Investigation of starch slurry concentration
[0037] Take the raw and auxiliary materials that meet the standards under the prescription of this product, fix the dosage of fermented Cordyceps powder, silicon dioxide, microcrystalline cellulose, and magnesium stearate, use 3-5%, 6-8%, 9-11%, and 12-14% corn starch slurry as a binder, and make granules according to the wet granulation method, press tablets, and coat. Take the granulation situation, plain tablet hardness, weight difference, disintegration time, friability, and reputation as the inspection indicators, and conduct a single factor inspection on the corn starch slurry concentration. The starch slurry inspection plan is shown in Table 5 below, and the quality evaluation is shown in Table 6 below:
[0038] Table 5 Starch slurry investigation plan (unit: g)
[0039]
[0040] Table 6 Quality evaluation
[0041]
[0042]
[0043] The test results show that: the soft material produced by batch 230401 is loose, with low hardness and poor reputation; the soft material produced by batch 230403 is sticky, the wet particles contain more coarse particles, and the reputation is medium; the soft material produced by batch 230404 is sticky, the reputation is good, but the weight difference is unqualified; the soft material produced by batch 230402 is suitable, all the test indicators are qualified, and the reputation is good, so batch 230402 is selected as the best solution, and 6-8% corn starch slurry is the best concentration.
[0044] Investigation on starch slurry preparation method and application temperature
[0045] 6-8% corn starch slurry was selected as the optimal concentration, and its unit prescription amount was 3000g / batch. The preparation methods of 6-8% corn starch slurry - boiling slurry method and flushing slurry method, as well as the effects of corn starch slurry use temperature of 50-60℃, 60-70℃, 70-80℃, and ≥80℃ on the reputation of Jinshuibao tablets were investigated. The investigation indicators were the granulation of the tablets, the hardness of the plain tablets, the weight difference, the disintegration time, the friability, and the reputation. The starch slurry preparation and use temperature investigation plan are shown in Table 7, and the quality evaluation is shown in Table 8:
[0046] Table 7 Starch slurry preparation method and use temperature investigation plan
[0047]
[0048]
[0049] Table 8 Quality evaluation
[0050]
[0051] The test results show that the temperature of the starch slurry of batch 230405 dropped to 50-60℃, and the skinning phenomenon occurred, resulting in the soft material containing small lumps, low hardness, and unqualified weight differences, and the reputation was evaluated as medium; the soft material produced by batch 230406 was suitable, the weight difference was qualified, but the hardness was low, and the reputation was evaluated as medium; the soft materials produced by batches 230407 and 230408 were scattered and had low hardness, resulting in a medium reputation; batch 230409 of starch When the slurry temperature dropped to 50-60℃, peeling occurred, resulting in small lumps in the soft material, moderate hardness, and good reputation, but unqualified weight difference; the soft materials prepared in batches 230411 and 230412 were loose and had low hardness, resulting in poor reputation; the soft material prepared in batch 230410 was suitable, with high hardness, qualified weight difference and good reputation, so the pulping method was preferred, and the use temperature of 60-70℃ was the optimal parameter for preparing starch slurry.
[0052] Study on the Preparation Method of Starch Slurry
[0053] The starch slurry was prepared by the slurry flushing method, and the temperature was 60-70°C. The unit prescription amount was 3000g / batch. The preferred corn starch slurry was investigated and allowed to stand and stirred to a temperature of 60-70°C. The stirring was performed using an overhead stirrer. The experimental scheme of the starch slurry preparation method is shown in Table 9 below, and the quality evaluation is shown in Table 10 below:
[0054] Table 9 Experimental scheme of starch slurry preparation method
[0055]
[0056] Table 10 Quality evaluation
[0057]
[0058] The test results show that the soft material prepared in batch 230413 is loose, has low hardness, and is rated as medium in reputation; the soft material prepared in batch 230414 is suitable, has high hardness, and is rated as good in reputation. Therefore, the method of using the slurry flushing method to obtain 6-8% corn starch slurry and stirring it with a stirrer to a temperature of 60-70°C is the most suitable method for preparing the adhesive for Jinshuibao tablets.
[0059] Experimental study on preparation technology of Jinshuibao tablets
[0060] Study on the amount of silicon dioxide used
[0061] Take the raw and auxiliary materials that meet the standards under the prescription of this product, fix the dosage of fermented Cordyceps powder and magnesium stearate, investigate the gradient of 5-7 parts, 8-10 parts and 11-13 parts of silicon dioxide as an oil absorbent, and adjust the amount of microcrystalline cellulose as a filler according to the theoretical preparation amount. The optimization test of silicon dioxide usage is carried out based on the granulation condition, hardness, weight difference, disintegration time, friability and reputation quality indicators. The optimization test plan of silicon dioxide usage is shown in Table 11 below, and the quality evaluation is shown in Table 12 below:
[0062] Table 11 Optimization test plan for silicon dioxide usage
[0063]
[0064] Table 12 Quality evaluation
[0065]
[0066]
[0067] The test results show that the soft materials prepared from batches 230501, 230502 and 230503 are sticky, with low hardness, unqualified weight difference and poor reputation; the soft materials prepared from batches 230504, 230505 and 230506 are loose, with low hardness and poor reputation; the soft materials prepared from batches 230507, 230508 and 230509 are suitable, with high hardness and good reputation. All other indicators meet the requirements. Therefore, 8-10 parts of silicon dioxide are preferred as the optimal usage of Jinshuibao tablets.
[0068] Study on the screening of glidants
[0069] Take the raw and auxiliary materials that meet the standards under the prescription of this product. Since 8-10 parts of silicon dioxide is the best dosage for Jinshuibao tablets, 9 parts of silicon dioxide are used as the feeding amount. Talc, magnesium stearate and silicon dioxide are used as glidants respectively, and a total of 15g is added for total mixing, tableting and coating. Take samples to conduct a single factor investigation on the type of glidant based on the quality indicators of hardness, particle repose angle, bulk density, weight difference, disintegration time and reputation. The screening plan for the type of glidant is shown in Table 13 below, and the quality evaluation is shown in Table 14 below:
[0070] Table 13 Screening scheme for types of flow aids
[0071]
[0072] Table 14 Quality evaluation
[0073]
[0074] The experimental results show that batch 230510 has the best fluidity, the best weight difference, low hardness, and a medium reputation; batch 230512 has poor fluidity, high hardness, and a good reputation, but the weight difference does not meet the requirements; batch 230511 has good fluidity, high weight difference and hardness, and a good reputation, so magnesium stearate in the prescription of batch 230511 was selected as the best glidant.
[0075] Investigation on the amount of glidant used
[0076] Take the raw and auxiliary materials that meet the standards under the prescription of this product, except for magnesium stearate, and feed the rest of the materials according to the prescription of batch 230511. Weigh different gradient amounts of 0.5%, 1%, and 1.5% magnesium stearate for total mixing, tableting, and coating. Take samples to conduct a single factor investigation on the amount of flow aid using the quality indicators of hardness, particle repose angle, bulk density, weight difference, disintegration time, and reputation. The investigation plan for the amount of flow aid is shown in Table 15 below, and the quality evaluation is shown in Table 16 below:
[0077] Table 15 Investigation plan of the amount of flow aid used
[0078]
[0079]
[0080] Table 16 Quality evaluation
[0081]
[0082] The experimental results show that the weight difference of batch 230515 does not meet the requirements and has a poor reputation; all evaluation indicators of batches 230513 and 230514 of Jinshuibao tablets meet the requirements, but the hardness of batch 230513 is 0.3kg higher than that of batch 230514, and the weight difference is more stable; therefore, the batch 230513 solution was selected, that is, 0.5% magnesium stearate was the optimal usage amount of the glidant.
[0083] Study on the stability of the pilot test of the preparation process of Jinshuibao tablets with better reputation
[0084] Take the raw and excipients under the prescription of this product that have been tested and meet the standards, and conduct a pilot test study in accordance with the 230513 batch prescription process, with a batch size of 7.5 kg and batch numbers 230601 to 230609. The pilot test plan is shown in Table 17 below, and the quality evaluation is shown in Table 18 below: Table 17 Pilot test plan
[0085]
[0086]
[0087] Table 18 Quality evaluation
[0088]
[0089] The experimental results show that the quality tests of the nine batches of pilot samples from 230601 to 230609 all meet the requirements, the production process is feasible and stable. The samples can enter the accelerated stability test phase.
[0090] Six-month accelerated stability study
[0091] The above nine batches of pilot Jinshuibao tablets were pressed into plates (12 tablets / plate) and the samples were subjected to accelerated stability test under the following conditions: temperature 40℃±2℃, relative humidity 75%±5% for 6 months. Samples were taken once in the 0th month, 3rd month, and 6th month of the test for testing. The results of the accelerated stability test are shown in Tables 19, 20, and 21 below:
[0092] Table 19 Results of accelerated stability study at month 0
[0093]
[0094]
[0095] Table 20 Results of the 3rd month accelerated stability study
[0096]
[0097] Table 21 Results of the 6th accelerated stability test
[0098]
[0099] Based on the above experimental results, it was concluded that the quality inspections of the nine batches of pilot samples from 230601 to 230609 at 3 and 6 months all met the requirements, and the reputation scores of Jinshuibao tablets were all good. The overall process of using corn starch slurry to replace gelatin solution is stable and feasible, and is suitable for promotion and application. DETAILED DESCRIPTION
[0100] The present invention is further illustrated by the following examples, but is not intended to be limiting of the present invention.
[0101] Embodiment 1, Jinshuibao tablets
[0102] Preparation method: Weigh 6 parts of corn starch in the prescription amount, add 2 times the amount of water to dissolve it, and prepare corn starch aqueous solution; slowly pour an appropriate amount of boiling water into the starch aqueous solution, stir while adding until it becomes a paste, and quantify to an appropriate amount to prepare 6% corn starch slurry; pour 60 parts of fermented Cordyceps powder, 24.5 parts of microcrystalline cellulose, and 9 parts of silicon dioxide into a high-speed mixing granulator and stir to mix well to prepare a dry mixed powder; slowly add 6% corn starch slurry to the dry mixed powder, wet mix, and add an appropriate amount of purified water according to the soft material to prepare a suitable soft material; put the soft material in a swing granulator to pass through an 18-mesh screen to prepare wet granules; put the wet granules on a stainless steel tray and place it in a constant temperature blast oven to dry the moisture to 4.2%, take it out, and prepare dry granules; put the dry granules in a swing granulator to pass through an 18-mesh screen to granulate, add 0.5 parts of magnesium stearate to mix, and obtain granules; tablet compression and film coating are obtained.
[0103] Embodiment 2, Jinshuibao tablets
[0104] Preparation method: weigh 8 parts of povidone K30 in the prescription amount, add appropriate amount of purified water, stir while adding until completely dissolved, and quantify to an appropriate amount to obtain 8% povidone K30 aqueous solution; pour 60 parts of fermented Cordyceps powder, 21 parts of microcrystalline cellulose, and 10 parts of silicon dioxide into a high-speed mixing granulator and stir to mix well to obtain a dry mixed powder; slowly add the 8% povidone K30 aqueous solution to the dry mixed powder, wet mix, and add appropriate amount of purified water according to the soft material to obtain a suitable soft material; place the soft material in a swing granulator to pass through an 18-mesh screen to obtain wet granules; put the wet granules on a stainless steel tray and place them in a constant temperature blast oven to dry the moisture to 4.5%, take them out, and obtain dry granules; place the dry granules in a swing granulator to pass through an 18-mesh screen to granulate, add 1 part of magnesium stearate to mix, and obtain granules; tablet press and film coat.
[0105] Embodiment 3, Jinshuibao Tablets
[0106] Preparation method: Weigh 5 parts of sodium carboxymethyl cellulose in the prescription amount, add appropriate amount of purified water, stir while adding until completely dissolved, quantify to an appropriate amount, and prepare 5% sodium carboxymethyl cellulose aqueous solution; pour 60 parts of fermented Cordyceps powder, 24 parts of microcrystalline cellulose, and 10 parts of silicon dioxide into a high-speed mixing granulator and stir to mix well to prepare a dry mixed powder; slowly add 5% sodium carboxymethyl cellulose aqueous solution to the dry mixed powder, wet mix, and add appropriate amount of purified water according to the soft material to prepare a suitable soft material; put the soft material in an oscillating granulator to pass through an 18-mesh screen to obtain wet granules; put the wet granules on a stainless steel tray and put them in a constant temperature blast oven to dry the moisture to 4.6%, take them out, and prepare dry granules; put the dry granules in an oscillating granulator to pass through an 18-mesh screen to granulate, add 1 part of magnesium stearate to mix, and obtain granules; press tablets, apply film coating, and obtain. Example 4, Jinshuibao Tablets
[0107] Preparation method: weigh 5 parts of hydroxypropyl methylcellulose in the prescription amount, add appropriate amount of purified water, stir while adding until completely dissolved, and quantify to an appropriate amount to obtain a 5% hydroxypropyl methylcellulose aqueous solution; pour 60 parts of fermented Cordyceps powder, 24 parts of microcrystalline cellulose, and 10 parts of silicon dioxide into a high-speed mixing granulator and stir to mix well to obtain a dry mixed powder; slowly add the 5% hydroxypropyl methylcellulose aqueous solution to the dry mixed powder, wet mix, and add appropriate amount of purified water according to the soft material to obtain a suitable soft material; place the soft material in a swing granulator to pass through an 18-mesh screen to obtain wet granules; put the wet granules on a stainless steel tray and place them in a constant temperature blast oven to dry the moisture to 4.8%, take them out, and obtain dry granules; place the dry granules in a swing granulator to pass through an 18-mesh screen to granulate, add 1 part of magnesium stearate to mix, and obtain granules; tablet compression and film coating are obtained.
[0108] Test Example 1. Pilot stability study of adhesive types suitable for the preparation of Jinshuibao tablets. The raw and auxiliary materials that meet the standards under the prescription of this product were taken and the batch prescription process was scaled up for pilot test according to the adhesive screening scheme in Table 1 above. The batch size was 7.5 kg and the batch numbers were 230610 to 230618. The pilot test scheme is shown in Table 22 below and the quality evaluation is shown in Table 23 below.
[0109] Table 22 Pilot test plan
[0110]
[0111] Table 23 Quality evaluation
[0112]
[0113]
[0114] The experimental results show that the quality tests of the nine batches of pilot samples from 230610 to 230618 all meet the requirements, the production process is feasible and stable. The samples can enter the accelerated stability test phase.
[0115] Six-month accelerated stability study
[0116] The above nine batches of pilot Jinshuibao tablets were pressed into plates (12 tablets / plate) and the samples were subjected to accelerated stability test under the following conditions: temperature 40℃±2℃, relative humidity 75%±5% for 6 months. Samples were taken once in the 0th month, 3rd month, and 6th month of the test for testing. The results of the accelerated stability test are shown in Tables 24, 25, and 26 below:
[0117] Table 24 Results of accelerated stability study at month 0
[0118]
[0119] Table 25 Results of the 3rd month accelerated stability study
[0120]
[0121] Table 26 Results of the 6th accelerated stability test
[0122]
[0123] Based on the above experimental results, it was concluded that the quality inspections of the nine batches of pilot samples from 230601 to 230609 at 3 and 6 months all met the requirements, and the reputation scores of Jinshuibao tablets were all medium. The overall process of using povidone K30, sodium carboxymethyl cellulose and hydroxypropyl methylcellulose to replace gelatin solution is stable and feasible, and is suitable for promotion and application.
Claims
1. A method for preparing Jinshuibao tablets, comprising the steps of preparing corn starch slurry; mixing three materials, namely, fermented cordyceps powder, microcrystalline cellulose and silicon dioxide; adding the corn starch slurry into the mixed materials by a slurrying method to prepare a soft material; preparing wet granules; preparing dry granules; granulating; adding magnesium stearate, mixing and then tableting.
2. The preparation method according to claim 1, characterized in that: Corn starch slurry is used as a binder during the preparation process.
3. The preparation method according to claim 1, characterized in that: The corn starch slurry is prepared by adding corn starch to water to prepare a corn starch slurry with a weight ratio of 6% to 8%.
4. The preparation method according to claim 1, characterized in that: The corn starch slurry is prepared into a corn starch slurry with a temperature of 60-70°C.
5. The preparation method according to claim 3, characterized in that: The Jinshuibao tablets have the following formula: The preparation method comprises the following steps: Weigh corn starch, add 2 times the amount of water to dissolve it, and prepare corn starch aqueous solution; slowly pour an appropriate amount of boiling water into the starch aqueous solution, stirring while adding until it becomes a paste, and quantitatively adjust to an appropriate amount to prepare 6-8% corn starch slurry; Pour fermented Cordyceps powder, microcrystalline cellulose and silicon dioxide into a high-speed mixing granulator and stir and mix to obtain dry mixed powder; slowly add 6-8% corn starch slurry at a temperature of 60-70°C into the dry mixed powder, wet mix, and add appropriate amount of purified water according to the condition of the soft material to obtain a suitable soft material; The soft material is placed in a swing granulator to pass through an 18-mesh screen to obtain wet granules; the wet granules are placed in a stainless steel tray and placed in a constant temperature blast oven to dry the moisture to 4-6%, and then taken out to obtain dry granules; the dry granules are placed in a swing granulator to pass through an 18-mesh screen to granulate; Add 0.5 parts of magnesium stearate into the mixture to obtain granules; compress into tablets and apply film coating to obtain the product.
6. The preparation method according to claim 1 or 2, characterized in that: In addition to corn starch as a binder, one or more of povidone K30, sodium carboxymethyl cellulose, and hydroxypropyl methylcellulose can also be used as a binder.
7. The preparation method according to claim 6, characterized in that: The following steps are involved: Weigh 8 parts of povidone K30 in the prescription amount, add appropriate amount of purified water, stir while adding until completely dissolved, and quantify to an appropriate amount to prepare an 8% povidone K30 aqueous solution; pour 60 parts of fermented Cordyceps powder, 21 parts of microcrystalline cellulose, and 10 parts of silicon dioxide into a high-speed mixing granulator and stir to mix well to prepare a dry mixed powder; slowly add the 8% povidone K30 aqueous solution to the dry mixed powder, wet mix, and add appropriate amount of purified water according to the soft material to prepare a suitable soft material; place the soft material in a swing granulator to pass through an 18-mesh screen to prepare wet granules; put the wet granules on a stainless steel tray and place them in a constant temperature blast oven to dry the moisture to 4.5%, take them out, and prepare dry granules; place the dry granules in a swing granulator to pass through an 18-mesh screen to granulate, add 1 part of magnesium stearate to mix, and obtain granules; tablet compression and film coating are performed.
8. The preparation method according to claim 6, characterized in that: The following steps are involved: Weigh 5 parts of sodium carboxymethyl cellulose in the prescription amount, add appropriate amount of purified water, stir while adding until completely dissolved, and quantify to an appropriate amount to obtain a 5% sodium carboxymethyl cellulose aqueous solution; pour 60 parts of fermented Cordyceps powder, 24 parts of microcrystalline cellulose, and 10 parts of silicon dioxide into a high-speed mixing granulator and stir to mix well to obtain a dry mixed powder; slowly add the 5% sodium carboxymethyl cellulose aqueous solution to the dry mixed powder, wet mix, and add appropriate amount of purified water according to the soft material to obtain a suitable soft material; place the soft material in a swing granulator to pass through an 18-mesh screen to obtain wet granules; put the wet granules on a stainless steel tray and place them in a constant temperature blast oven to dry the moisture to 4.6%, take them out, and obtain dry granules; place the dry granules in a swing granulator to pass through an 18-mesh screen to granulate, add 1 part of magnesium stearate to mix, and obtain granules; tablet compression and film coating are performed to obtain.
9. The preparation method according to claim 6, characterized in that: The following steps are involved: Weigh 5 parts of hydroxypropyl methylcellulose in the prescription amount, add appropriate amount of purified water, stir while adding until completely dissolved, and quantify to an appropriate amount to obtain a 5% hydroxypropyl methylcellulose aqueous solution; pour 60 parts of fermented Cordyceps powder, 24 parts of microcrystalline cellulose, and 10 parts of silicon dioxide into a high-speed mixing granulator and stir to mix well to obtain a dry mixed powder; slowly add the 5% hydroxypropyl methylcellulose aqueous solution to the dry mixed powder, wet mix, and add appropriate amount of purified water according to the soft material to obtain a suitable soft material; place the soft material in a swing granulator to pass through an 18-mesh screen to obtain wet granules; put the wet granules on a stainless steel tray and place them in a constant temperature blast oven to dry the moisture to 4.8%, take them out, and obtain dry granules; place the dry granules in a swing granulator to pass through an 18-mesh screen to granulate, add 1 part of magnesium stearate to mix, and obtain granules; tablet compression and film coating are performed.